Peran Change Agent pada Organisasi BUMN dengan mengambil studi kasus pada PT. Indonesia Power sebagai salah satu anak perusahaan BUMN - Ian Rico Andreas Ricardo; H. Thatok Asmony; Dwi Putra Buana Sakti (Yayasan Pendidikan Intan Cendekia, 2022)
The role of Change Agent is usually always played by company leaders or managers who have leadership positions and are part of top management. The purpose of this study was to determine the role of change agents in BUMN organizations by taking a case study at PT. Indonesia Power as one of the largest BUMN subsidiaries in Indonesia, namely PT PLN (Persero). This study used qualitative research methods. Informants in this study are organic employees of PT. Indonesia Power which has the decision to determine as a Change Agent from the Board of Directors of PT. Indonesia Power with a term of office between 2017 to 2021. Data collection techniques used interview, observation, and documentation guidelines. Data were analyzed using qualitative analysis methods. Based on the analysis and results, it can be concluded as follows: Change Agent characteristics demands that must be owned by PT. Indonesia Power, which includes creativity, insight, passion for work, discipline, empathy, and flexibility. The role of a Change Agent as a non-structural employee within PT. Indonesia Power includes as a consultant, as a trainer, as a catalyst, as a mover, as a solution provider, and as a mediator. The challenges faced in acting as a Change Agent within PT. Indonesia Power includes resistance (resistance to change) and readiness to change (readiness to change).